Ethnoagriculture of Cirendeu traditional village, Cimahi, West Java: Local knowledge implementation on agricultural practices - Primasongko, Akbar; Raihandhany, Reza (Genbinesia Journal of Biology, 2022)
Cireundeu Traditional Village (Kampung Adat Cireundeu) is a unique village located in Cimahi City, West Java. This village is the house to the traditional community that make use of local or traditional knowledge to maintain their natural resources. They are well known to consume cassava rice (“rasi”, abv. beras singkong) as staple food. They also have strict traditional rules regarding spatial management in land usage. This paper aims to explain the ethnoagriculural aspects of Cireundeu’s traditional community, to determine the strengths and weaknesses of their practices, and to suggest further action to their common problems. The methods used are literature reviews from various scientific sources. From the reviews, Cireundeu’s traditional community ethnoagriculture aspects are shown by the integration of traditional rules to determine land use and producing agricultural crop and implement sustainable agriculture. While their tradition helps them self-fulfill their daily lives, this community also faced several threats from the outside, such as housing development and long term effect from Leuwigajah Final Land Disposal. These results suggest the needs for further studies on these long term effects and outside influence to help Cireundeus’s community preserving their heritages.